The Immunological Roles of Olfactory Ensheathing Cells in the Treatment of Spinal Cord Injury - Jiang, Yizhen; Guo, Jianbin; Tang, Xiangwen; Wang, Xiaohui; Hao, Dingjun; Yang, Hao (Frontiers in Immunology, 2022)
Spinal cord injury (SCI) is a devastating type of neurological disorder of the central nervous system (CNS) with high mortality and disability. The pathological processes of SCI can usually be described as two stages, namely, primary and acute secondary injuries. Secondary injury produces more significant exacerbations of the initial injury. Among all the mechanisms of secondary damage, infection and inflammatory responses, as the principle culprits in initiating the second phase of SCI, can greatly contribute to the severity of SCI and numerous sequelae after SCI. Therefore, effectively antagonizing pro-inflammatory responses may be a promising treatment strategy to facilitate functional recovery after SCI. Olfactory ensheathing cells (OECs), a unique type of glial cells, have increasingly become potential candidates for cell-based therapy in the injured CNS. Strikingly, there is growing evidence that the mechanisms underlying the anti-inflammatory role of OECs are associated with the immune properties and secretory functions of these cells responsible for anti-neuroinflammation and immunoregulatory effects, leading to maintenance of the internal microenvironment. Accordingly, a more profound understanding of the mechanism of OEC immunological functions in the treatment of SCI would be beneficial to improve the therapeutic clinical applications of OECs for SCI. In this review, we mainly summarize recent research on the cellular and molecular immune attributes of OECs. The unique biological functions of these cells in promoting neural regeneration are discussed in relation of the development of novel therapies for CNS injury.